Prediction of recurrent venous thromboembolism by measuring ProC Global - Eichinger, Sabine; Hron, Gregor; Hirschl, Mirko; Bialonczyk, Christine; Minar, Erich; Kollars, Marietta; Kyrle, Paul A. (Thrombosis and Haemostasis, 2007)
In patients with venous thromboembolism (VTE) a laboratory assay that globally measures the overall thrombophilic tendency is not available. We hypothesized that determination of ProC® Global, a plasma assay which tests the global function of the protein C pathway, could be used to stratify patients according to their risk of recurrent VTE. We prospectively followed 774 patients with first spontaneous VTE for a mean time of 52 months. ProC Global normalized ratio (NR) was measured in plasma by use of a commercially available assay based on activated partial thromboplastin time. Ninety-eight of the 774 patients had recurrent VTE. Patients with ProC Global NR ≥ 0.75 had a relative risk of recurrence of 0.59 (95% CI 0.40–0.87) as compared with those with lower ratio. After four years, cumulative probability of recurrence was 8.6% in patients with ProC Global NR ≥ 0.75 and 17.4% in patients with a lower ratio (p=0.006). Patients with a high ProC Global NR have a low risk of recurrent VTE. ProC Global NR can be used to stratify patients with a first unprovoked VTE according to their risk of recurrence.
Keywords: Venous thrombosis; recurrence; ProC Global